2009
DOI: 10.1124/dmd.109.029843
|View full text |Cite
|
Sign up to set email alerts
|

If the KI Is Defined by the Free Energy of Binding to P-Glycoprotein, Which Kinetic Parameters Define the IC50 for the Madin-Darby Canine Kidney II Cell Line Overexpressing Human Multidrug Resistance 1 Confluent Cell Monolayer?

Abstract: ABSTRACT:From previous fits of drug transport kinetics across confluent Madin-Darby canine kidney II cell line overexpressing human multidrug resistance 1 cell monolayers, we found that a drug's binding constant to P-glycoprotein (P-gp) was significantly smaller than its IC 50 when that drug was used as an inhibitor against another P-gp substrate. We tested several IC 50 candidate functions, including the standard function, the Kalvass-Pollack function, and the efflux ratio, to determine whether any of them yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…In the absence of inhibitor, cell line 2 will have a smaller intracellular probe substrate concentration than cell line 1, so the fraction of P-gp with substrate bound to it in the absence of inhibitor will be smaller in cell line 2. This means that more inhibitor will have to be added to cell line 2 to reduce the fraction of P-gp with substrate bound to it by 50% (Lumen et al, 2010). Thus, the IC 50 value for cell line 2 will be higher than the IC 50 value for cell line 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of inhibitor, cell line 2 will have a smaller intracellular probe substrate concentration than cell line 1, so the fraction of P-gp with substrate bound to it in the absence of inhibitor will be smaller in cell line 2. This means that more inhibitor will have to be added to cell line 2 to reduce the fraction of P-gp with substrate bound to it by 50% (Lumen et al, 2010). Thus, the IC 50 value for cell line 2 will be higher than the IC 50 value for cell line 1.…”
Section: Discussionmentioning
confidence: 99%
“…B1 (green squares) and D (black circles), with the exception of Inhibitor 15 (verapamil). It has been noted previously for MDCKII-MDR1 cells as well as LLC-PK 1 -MDR1 cells (Lumen et al, 2010, Sugimoto et al, 2011) that an IC 50 based on transport activity expressed as an efflux ratio (eq. A1 or A2) is typically lower than one based on B.A transport (B1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the confluent cell monolayer, when the dissociation constant of the inhibitor to P-gp is denoted K I , we have shown that the ratio of the IC 50 / K I increases with increased P-gp surface density and probe-substrate elementary efflux rate constants and decreases with the contributions of other probe-substrate transporters [28]. The simple IC 50 analysis is very different with confluent cell monolayers, or tissue, than it is with water soluble enzymes, upon which the standard IC 50 equation were tested [28].…”
Section: Introductionmentioning
confidence: 95%
“…However, a second study measuring the cellular efflux of the P-gp substrate doxorubicin in MDR1 expressing B16/10 murine melanoma cells reported that propiconazole inhibited P-gp transport significantly less than verapamil (Bain and LeBlanc,1996). Such differences are not unexpected as P-gp and other endogenous transporters may be expressed at varying levels between cell line and passage number (Lumen et al, 2010). In addition, differing physicochemical properties of probe substrates can influence the potency of a xenobiotic to inhibit P-gp transport in a given assay (Zastre et al, 2008).…”
Section: Discussionmentioning
confidence: 98%